KEPUASAN PENGGUNA TERHADAP MANAJEMEN PEMBAYARAN DI FAKULTAS SYARIAH UIN PALOPO BERBASIS CLOUD SYSTEM - Arniati Amru; Baderiah Baderiah; Kaharuddin Kaharuddin; Nurzykila Nurzykila (STKIP Pesisir Selatan, 2026)
This study aims to analyze user perception of cloud-based payment systems at the Faculty of Sharia UIN Palopo based on the dimensions of Perceived Usefulness and Perceived Ease of Use in the Technology Acceptance Model (TAM). Digital transformation in higher education administration services requires an effective, efficient, and easy-to-use payment system, so it is important to evaluate user admissions. This study uses a quantitative approach with a survey method. The research sample amounted to 84 respondents consisting of students and administrative staff of the Faculty of Sharia UIN Palopo. The sampling technique uses probability sampling through the proportionate stratified random sampling method. Data were obtained through questionnaires and analyzed using descriptive statistics, validity tests, and reliability tests with the help of SPSS version 29. The results showed that the Perceived Usefulness variable obtained an average value of 3.91 and the Perceived Ease of Use variable of 3.86, both of which were in the good category. These findings show that cloud-based payment systems are considered to be able to speed up the payment process, facilitate access to transaction information, improve administrative efficiency, and are easy to understand and use by users. The results of the validity test showed that all instrument items were valid with the value of r calculated > r of the table, while the reliability test obtained a Cronbach's Alpha value of 0.977 which indicates that the instrument is very reliable.